The sky is falling! - Teague, Mark (Orchard Books, an imprint of Scholastic Inc., 2015)
In this humorous version of the traditional tale, Chicken Little panics when an acorn falls on her head and sets off a dance frenzy among the other chickens, and while squirrel and the other animals understand what really happened, they soon join in the dancing--because it is fun.